Developing an English communicative competence training course for non-English-major teachers in Thailand - Nithitwaraphakun, Kannaphat (International Journal of Psychosocial Rehabilitation, 2020)
In the contemporary communicative landscape and for the foreseeable future, professionals need to be competent users of English given that this language is used worldwide. On this basis, the Association of Southeast Asian Nations (ASEAN) has designated English a “working language” among ASEAN countries. Further, the government of Thailand requires that all Thai students learn English as their first foreign language. However, this is problematic inasmuch as most English teachers, particularly those teaching at the primary level, did not graduate with a major in English. Therefore, they are unlikely to be able to provide the most effective instruction to their students. This study focuses on developing English communicative competence training courses for and evaluating the English communicative competence of non-English-major teachers in Thailand. The training course was developed and designed in reference to seven elements: (1) the principles and significance of the training course, (2) objectives, (3) structure of the program, (4) activities and duration (5) the media used during the training course, (6) assessment, and (7) expected benefits. On completing the course, the participants’ scores on an English language test improved significantly, by 0.05 on average. The participants’ scores for all elements of English pronunciation and communication in the classroom were higher after the training course than before it. Further, the participants reported a high level of satisfaction with the program, with an average value of 4.50 and a standard deviation of 0.47. Overall, the program was shown to benefit the development of English communication competence on the part of English teachers without a degree in English.